Rapid detection of antimicrobial residues in broiler meat using flow cytometry-driven multiplex immunoassay - Cannizzo, Francesca Tiziana; Sini, Federica; Divari, Sara; Cuccato, Matteo; Poggi, Alessia; Panseri, Sara; Nobile, Maria; Chiesa, Luca Maria; Riondato, Fulvio (Frontiers in Veterinary Science, 2025)
IntroductionThe misuse of antimicrobials (AMs) in poultry production contributes significantly to the global threat of antimicrobial resistance. Despite legislative efforts within the European Union (EU) to reduce AM use, Italy remains among the countries with the highest consumption levels. Effective and accessible screening tools for AMs residues in poultry meat are crucial for food safety monitoring and regulatory compliance. This study evaluates the performance of the Beadyplex flow cytometric assay as a field-applicable method to detect residues of thiamphenicol, sulphadiazine, and amoxicillin in broiler chicken skeletal muscle.MethodsPectoralis major muscle samples were collected from 41 male broiler chickens (Ross 308) previously treated with thiamphenicol (n = 11), sulphadiazine (n = 6), amoxicillin (n = 12), or untreated (controls, n = 12). Beadyplex assays were performed following manufacturer instructions, and results were acquired using a standard flow cytometer. Sensitivity, specificity, predictive values, and kappa agreement were calculated to assess the performance of the test in recognizing the AMs treatment. The agreement with the current reference method for detecting AM residues (high-performance liquid chromatography–high-resolution mass spectrometry, or HPLC-HRMS) was also calculated.ResultsThe Beadyplex assay demonstrated high sensitivity and specificity for thiamphenicol (Se = 1.00; Sp = 0.83; k = 0.791) and sulphadiazine (Se = 1.00; Sp = 0.91; k = 0.813), with substantial to almost perfect agreement with HPLC-HRMS results (k = 0.706 and 0.827, respectively). Amoxicillin residues were not detected in any treated sample by Beadyplex.DiscussionThe Beadyplex assay offers a promising, cost-effective, and rapid screening complementary to confirmatory analysis for detecting selected AM residues in poultry meat. Its substantial agreement with reference methods and ease of use with standard cytometers support its potential application in field-based veterinary surveillance and food safety programs.